PEDOGOGICAL ASPECTS OF THE DEVELOPMENT OF ANALYTICAL THINKING IN STUDENTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
It is known that the social and economic spheres of society: updates in the preparation of comprehensively mature specialists for the areas of Science Technology, Culture and education have caused the problem of developing creative thinking in students in higher educational institutions. Therefore, during the period of intensive growth of current scientific and scientific and technical information, in the conditions of changing and updating knowledge within various disciplines, as well as the rapid penetration of modern technologies into all areas, the training of “highly qualified competitive personnel” in higher educational institutions in the directions, especially their independent scientific and creative approach to each work, Active Thinking, After all, today a specialist who cannot think creatively will not be able to adapt to the rapidly changing conditions of Science, Technology, Technology and will have difficulty organizing successful activities.